The highly conserved C-terminal end segment of troponin T binds tropomyosin and actin to function in modulating contractile kinetics - Tianxin Cao; Han-Zhong Feng; Jayant James Jayasundar; J.-P. Jin (Proceedings of the National Academy of Sciences, 2025)
The troponin (Tn) complex plays a central role in regulating striated muscle contraction and relaxation. Troponin T (TnT) and troponin I (TnI) are two of the three subunits of Tn, which have evolved from a TnI-like ancestor gene. Proteolytic removal of the evolutionarily added N-terminal variable region of cardiac TnT, as occurs in acute ventricular contractility-afterload mismatch, brings back a TnI-like molecular conformation and function to reduce ventricular systolic velocity, elongates ejection time, and sustains stroke volume. Investigating the underlying mechanism found in addition to the two previously known tropomyosin (Tm)-binding sites another Tm-binding site in the highly conserved C-terminal end segment of TnT, which is also an F-actin binding site. Its functionality is retained in the form of free peptide with an effect on cardiac muscle contractile kinetics. Hypertrophic cardiomyopathy mutations in this segment significantly decrease Tm-binding affinity. The finding of a third Tm-binding site and localizing the actin-binding site of TnT revise our understanding of the dynamic interactions between Tn and actin thin filament with physiological and pathophysiological implications.